Comparative Study and Analysis of DSR, DSDVAND ZRP in Mobile Ad-Hoc Networks - Kachal, Ritika; Suri, Shrutika (International Journal of Computer Sciences and Engineering, 2014)
Wireless networks where mobile nodes relay on each other to keep network connected without help of pre-existing infrastructure or centralized control are the mobile ad-hoc networks. These are the self organizing temporary wireless networks. An efficient and effective routing protocol for real MANETs is a major design issue, therefore to achieve optimum values of performance parameter under network scenarios where nodes are subjected to different type of mobility that dynamically change the network topology. Due to the link instability and mobility of node, the topology of ad-hoc network changes and routing become difficult. Many ad-hoc routing protocols have been proposed in the recent years. These protocols can be classified in three main categories: proactive, reactive and hybrid routing protocols. In this paper study of these existing routing protocols is done and comparison analysis of DSDV, DSR and ZRP is performed.